THE EMERGENCE OF WOMEN AS HISTORICAL SUBJECTS: DECONSTRUCTING THE HISTORY OF SPAIN FROM TEXTBOOKS - Peinado Rodríguez, Matilde (Historia y Memoria de la Educación, 2024)
The work we present is not an analysis of the presence of women in textbooks, a very fruitful historiographical line from which magnificent works have been published in recent years. The methodology is logical-argumentative and qualitative, where the written and visual contents of the textbooks are the pretext to rethink/deconstruct History in the light of the gender perspective. We start from an evolutionary analysis of the presence of women in the current manuals of History of the second year of Baccalaureate, for the period from 1931 to 1975, to understand the keys to the inclusion/exclusion of the female collective in the historical narrative and to propose how the conception of citizenship present in the LOMLOE can become a challenge and an opportunity to rethink and, Consequently, to rewrite a subject that continues to be largely articulated from androcentrism, patriarchy and classism, although its main mission is to develop the critical thinking of students and prepare them to think historically and act socially. We present, for this, a conceptual proposal that necessarily starts from an epistemological deconstruction of history as a science. For this, we have taken as a reference a representation of the research published in recent years that make visible the significance of women in the historical story, with the aim of outlining the thematic lines that allow us to move towards history free of androcentric and patriarchal biases, where women are integrated and made visible as historical subjects.